IMPLEMENTASI METODE PROMETHEE PADA PEMILIHAN REGISTRAR DOMAIN DI INDONESIA - Maha'd Wicaksono; Maulana Ighsan Lucky (JURNAL ILMIAH INFORMATIKA, 2023)
A domain registrar is a commercial company whose job is to register domain names that have been registered with ICANN (Internet Corporation for Assigned Names and Numbers) or maintain domain ccTLDs that involve certain country codes. Domain registration is the first step in website development as an effort to the existence of a business entering the digital economy era. To ensure the continuity of a business in the internet world, the selection of a domain registration service is very important. Because the domain is the identity as well as the address of a business on the internet. Domain registration service organizations must meet various important criteria needed as a professional domain registration service. These criteria must be able to answer the crucial characteristics of a domain registrar. This study uses PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation). The PROMETHEE method is used to rank among all alternatives based on predetermined criteria. The stages of problem solving in this study are determining alternatives, determining criteria, to ranking alternatives, so that will produce the best alternative output. In this study the PROMETHEE calculation results obtained with the best alternative output being the Domainesia registrar with a net flow value of 0.592.